PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP KOMPETENSI SERTA DAMPAKNYA PADA KINERJA PRAMUWISATA BALI - Purnomo, Danang; Sudana, I Putu; Sasrawan Mananda, I GPB. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 4 No 2 (2016): Jurnal IPTA (December 2016), 2016)
This research aims to discuss about the influences of tour guides education and training towards competencies and the impact direct and indirect to performance. It is used mix combination between qualitative and quantitative research with concurrent embedded models. This research used data primary and secondary data. Data collected by observation, interview and spreading questionare to 99 tour guides. Analysis data used path analysis with a single path. The result of this research is education and training has positive and significant influence towards competencies Balinese tour guides with coefficient values 0,802 . Competency has positive and significant influence towards performance Balinese tour guides with coefficient value 0,563 . Education and training has positive and significant influence toward performance directly with coefficient value 0,279 . Education and training through competencies has positive and significant influence toward performance indirectly with sum total coefficient value 0,731. Suggestions for academic expected to research reenacting with same model to verifying result of the study . The suggestion for stakeholder related tour guides profession is to increasing education and training programme of tour guides for increasing competencies and performance of Balinese tour guides.
Keywords: Education and Training, Competency, Performance, Tour Guide